22nd AIAA Computational Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-2755
|View full text |Cite
|
Sign up to set email alerts
|

A Mapped Chebyshev Pseudospectral Method for Unsteady Flow Analysis

Abstract: A mapped Chebyshev pseudospectral method is developed as an accurate and yet efficient approach to solve unsteady flows. Preserving the conservation laws, the method discretizes a spatial derivative term implicitly while a time derivative term is treated explicitly using the mapped Chebyshev collocation operator. As standard Chebyshev points make the corresponding spectral derivative matrix ill-conditioned due to uneven distribution of the Chebyshev points clustered heavily towards the ends of the interval, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Moreover, it is reported in the reference paper [23] that unsteady flows around an airfoil plunging at constant speed with nonzero freestream velocity are equivalent to steady flows of an stationary airfoil fixed at a certain angle of attack with the same freestream velocity, which is explained graphically in Figures 6(a) and 6(b). An overset mesh topology for the plunging airfoil is constructed to facilitate the dynamic motion of the airfoil with a near-body grid of 257 × 45 and a background grid of 301 × 151 as shown in Figure 7.…”
Section: Plunging Airfoil One Of the Biggest Advantages Of Thementioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, it is reported in the reference paper [23] that unsteady flows around an airfoil plunging at constant speed with nonzero freestream velocity are equivalent to steady flows of an stationary airfoil fixed at a certain angle of attack with the same freestream velocity, which is explained graphically in Figures 6(a) and 6(b). An overset mesh topology for the plunging airfoil is constructed to facilitate the dynamic motion of the airfoil with a near-body grid of 257 × 45 and a background grid of 301 × 151 as shown in Figure 7.…”
Section: Plunging Airfoil One Of the Biggest Advantages Of Thementioning
confidence: 93%
“…* is the nondimensional time and Reynolds number based on the chord length is 5.5 × 10 6 . For the pseudo time integration, the mapped Chebyshev spectral derivative term, a DADI (diagonal alternate direction implicit), method is applied [15,23,31]. A Roe's upwind flux-difference splitting (FDS) method [32] is employed for the flux term discretization with a third order MUSCL scheme to improve solution accuracy.…”
Section: Pitching Airfoil With a Given Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…The computational expenses increase rapidly with the number of harmonics. Hall et al [1] suggested an alternative way to resolve such problems by casting inverse Fourier transformation to (10) as shown in…”
Section: Time-spectral Methodsmentioning
confidence: 99%
“…Im et al [10] solved two-dimensional airfoil flows under forced oscillation by the Euler and Navier-Stokes solvers with the mapped Chebyshev pseudospectral method. The results obtained very similar characteristics compared to those of the Fourier pseudospectral method in terms of both solution accuracy and computational efficiency.…”
Section: Introductionmentioning
confidence: 99%